Adherence to cancer prevention recommendations is associated with a lower breast cancer risk in black urban South African women. Issue 6 (28th March 2022) - Jacobs, Inarie; Taljaard-Krugell, Christine; Wicks, Mariaan; Cubasch, Herbert; Joffe, Maureen; Laubscher, Ria; Romieu, Isabelle; Biessy, Carine; Gunter, Marc J.; Huybrechts, Inge; Rinaldi, Sabina
Abstract: Breast cancer prevention is of great importance to reduce high incidence in South Africa. This study aimed to investigate adherence to the 2018 World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) Cancer Prevention Recommendations and the association with breast cancer risk in black urban women from Soweto, South Africa. A total of 396 breast cancer cases and 396 population-based controls from the South African Breast Cancer study (SABC) matched on age and demographic settings were included. Validated questionnaires were used to collect dietary and epidemiological data. To assess adherence to these recommendations, an eight-point adherence score was developed, using tertiles among controls for scoring each recommendation (0, 0·5 and 1) with zero indicating the lowest adherence to the recommendations. OR and 95 % CI were estimated using multivariate logistic regression models to analyse associations between the WCRF/AICR score and breast cancer risk. Greater adherence (>4·5 v . <3·25) to the 2018 WCRF/AICR Cancer Prevention Recommendations was associated with a significant inverse association with breast cancer risk overall (OR = 0·54, 95 % CI 0·35, 0·91) and specifically in postmenopausal women (OR = 0·55, 95 % CI 0·34, 0·95), in cases with oestrogen positive and progesterone positive breast cancer subtypes (OR = 0·54, 95 % CI 0·39, 0·89 and OR = 0·68, 95 % CI 0·43, 0·89, respectively) and in obese women (OR = 0·52, 95 % CI 0·35, 0·81). No significant association with breast cancer risk was observed in premenopausal women. Greater adherence to the 2018 WCRF/AICR Cancer Prevention Recommendations may reduce breast cancer risk in this black urban population of Soweto. Adherence thereof should be encouraged and form a part of cost-effective breast cancer prevention guidelines.